POLA TATA LETAK SITUS TRADISI MEGALITIK DI DAS SEKAMPUNG - Rr. Triwurjani (BRIN, 2000)
From research on earthen structures, it can be seen that the megalithic settlements in the Sekampung watershed are settlements built by making trenches and mounds of land. These settlements can be made by building mounds of land and trenches or just ditches, the shape of the land surface of these settlements is different. Some follow the existing patterns of natural formation and some are not. Some are located close to the main river and some are far from the main river. Sites located on major rivers include the Pejambon, Gedig, Parigi and Meris sites; while the sites located on the Sekampung tributary are the sites of Gelombang, Pugung Raharjo, Cicilik, and Bentengsari. The shape of the site that does not follow the landscape and has an orderly shape is the Parigi site.